Enhancing Learning And Performance In Framework Documentation Using Use Case Map - Hee, Wei Loon (2016)
Framework documentation is a process whereby a framework is documented in a proper manner so that it could be easily reused in any future application development. Two main documentation styles have been included in this study – Patterns and Minimalist styles. It is not easy to document a framework well. Therefore, well-established theories or rules to follow when documenting are helpful. The aim of this study is to discover a new method that can improve the learning curve and to make mass learning possible among users in framework documentation. It focuses on Minimalist and Patterns theory but with a new add-on approach - augmented with Use Case Maps (UCM). Patterns have the idea of providing the solution to a problem in its context. It has contextual information which is not minimal, unlike Minimalist. Minimalist documentation promotes minimal reading and random-access which means that the learner can proceed in a self-directed manner as well as using small pages that can be read as according to the learner’s desires on the reading order. The use of UCM in these documentation styles has been examined in detail using a qualitative research method to prove that UCM is more effective in allowing learners to perform efficiently and understand the framework better than documentation without UCM.